A redução da jornada de trabalho como fator implementador do direito à saúde e ao lazer do trabalhador - Lima, Fábio Nunes de (2013)
The objective of this investigation is to analyze the reduction of working hours as an implementing factor for the realization of workers social rights to health and recreation. Firstly, we introduce the concepts of the "duration of working time" and "working hours", followed by a study of their historical evolution, in Brazil and abroad. The chapter The Benefits of Working Hours Reduction covers both the direct benefits related to the rights to health and leisure and the indirect ones related to the generation of jobs and consequent heating of the economy. The realization of social rights to health and leisure - part of the Rights and Fundamental Guarantees laid down by the Constitution of 1988 - requires further analysis. We also address some issues like the commercialization of the workers health and the recommendation of the International Labor Organization (ILO) for a 40-hour working week, based on documents and international legislation. The possibility of the current working hours be reduced through collective bargaining is evaluated in light of the specificities of the Brazilian union system. Finally, this study examines a number of legislative proposals aimed at reducing the working hours in Brazil. Among them, we highlight the Constitutional Amendment 231 project, since it is in line with the present investigation as far as proposing a 40-hour workweek as a way to effectively materialize the right to health and leisure of Brazilian workers